Penerapan Model Pembelajaran Talking Stick Untuk Meningkatkan Hasil Belajar Bahasa Indonesia di Kelas IV SD Inpres Leleko - Mersty E. Rindengan (Peneliti.net, 2021)
This research was conducted based on preliminary observations carried out in class IV of SD INPRES Leleko where it was found that in classroom learning the teacher had not utilized his abilities to the fullest in using the right learning model in teaching. This makes students bored and unenthusiastic about learning because the learning process is only teacher-centered. This study aims to improve students' learning outcomes in INDONESIAN LANGUAGE through the application of the Talking Stick learning model. The research design used is Classroom Action Research. The subjects of this study were 15 grade IV students of SD INPRES Leleko. The data collection technique used is observation and testing. The data analysis technique used is presentation. Based on the results of the study, it was shown that in the first cycle, student learning outcomes only reached 64.66%. Because it was found that there were still many students who did not understand the meaning of the questions, the researchers continued in cycle II and student learning outcomes increased to 87.33%. Referring to the results of this study, it was concluded that the application of the Talking Stick learning model to the Indonesian language subject in written material can create a fun learning atmosphere, and involve students as a whole in learning so that students do not feel bored while learning.